2007
DOI: 10.1088/0953-8984/19/41/415114
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oxide additions on medium-range order structures in borosilicate glasses

Abstract: Boron-11 nuclear magnetic resonance (MAS NMR) and Raman spectroscopies have been used to study four families of glasses: xCsO(100-x)ZMW (0 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…2(a)) were fitted in most cases with two Gaussian lines: one Q 3 peak and one Q 4 (B) peak, representing silicon atoms with predominantly two Si and two B next nearest neighbors [20]. Contributions from Q 2 units were negligible for all but typically the highest Cs 2 O contents and the high MgO content system.…”
Section: Si Mas Nmr Spectramentioning
confidence: 99%
“…2(a)) were fitted in most cases with two Gaussian lines: one Q 3 peak and one Q 4 (B) peak, representing silicon atoms with predominantly two Si and two B next nearest neighbors [20]. Contributions from Q 2 units were negligible for all but typically the highest Cs 2 O contents and the high MgO content system.…”
Section: Si Mas Nmr Spectramentioning
confidence: 99%
“…The danburite glass lost 12 ± 2% mass and the reedmergnerite lost 4 ± 2%. The occurrence of these two superstructural units in glasses is discussed in more depth in [37].…”
Section: Nmr and Volatilization Measurementsmentioning
confidence: 99%
“…29 Si MAS NMR of borosilicate glasses has enabled the identification of the Q n fractions (n denoting the number of bridging oxygens). Most commonly these are observed as Q 4 , Q 3 and Q 4 (B) units, where (B) indicates 3Si + 1B or 2Si + 2B next nearest neighbors [37]. Q 2 sites are only possible when there is sufficient alkali oxide associated with the silicate network that the ratio of alkali oxide to silica exceeds 1:2.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrex @ , or optical glasses and also for storage of nuclear waste. A considerable amount of results have been obtained about the structure of these glasses [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], mainly via NMR analyses of 11 B, 17 O, 23 Na and 29 Si, Raman spectroscopy and neutron diffraction [18]. A comprehensive model was proposed almost 30 years ago in the present journal by Yun and Bray, Yun et al [1,2] and by Dell et al [3], based on experimental 11 O 3 ] (where [Á] mol%) are the most important composition-related structural parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Although this model is still a valuable starting reference for the structure evolution as alkali cations are added to the glass system, several authors have criticized it. In particular, some recent publications [4][5][6][7][8][15][16][17][18][19], have shown that in general alkali cations are more randomly mixed to the borate and silica networks than was assumed in [1][2][3]. At a quantum level, it is not always true that exactly one Na + is needed to compensate the charge of one BO À 4 unit [13], so it is not fully correct to assume the value R = 0.5 as a starting point for the formation of borosilicate units.…”
Section: Introductionmentioning
confidence: 99%